The story of civilization - Durant, Will (Simon and Schuster, 1942)
This is the classic reference on world history, recognized as the most comprehensive general history ever written, the result of four decades of work by Will and Ariel Durant -- a set that The New York Times called "a splendid, broad panorama of hereditary culture in words and images that the layman can fully understand." This series began as an effort to write a history on the nineteenth century, an undertaking that Will Durant realized could only be understood in terms of what had come before. So the Durants embarked on an encyclopedic survey of all civilization, ancient and modern, Occidental and Oriental.